2011
DOI: 10.5767/anurs.cmat.110201.en.088k
|View full text |Cite
|
Sign up to set email alerts
|

Thermographic Testing of Epoxy-Glass Composite Tensile Properties

Abstract: Abstract:The results obtained in the parallel testing of the epoxy-glass composite specimen, using conventional mechanical methods and thermography, are presented. The tensile properties of composite were followed by thermography. The temperature changes on the tested sample were continuously recorded enabling the prediction of the critical stresses, which might cause the fractures and to define the criteria on the maximum sample temperature alteration in the field of the elastic and elastic-plastic deformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The temperature distribution for both specimens consist of two phases, as illustrate in Figure 6. Each phase of temperature distribution has different behaviour [17,28,29,30]. The first phase of the elastic phase generates a decreasing trend of temperature behaviour due to the absorption energy by the specimen from the given load.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature distribution for both specimens consist of two phases, as illustrate in Figure 6. Each phase of temperature distribution has different behaviour [17,28,29,30]. The first phase of the elastic phase generates a decreasing trend of temperature behaviour due to the absorption energy by the specimen from the given load.…”
Section: Resultsmentioning
confidence: 99%
“…where, α1 and α2 are the coefficients of thermal expansion (μm/m o C), Cp is the specific heat at constant pressure (J/g o C), ρ is density (g/cc) and Δσ is the change in stress (N/m 2 ) where subscripts 1 and 2 denote the longitudinal and transverse to fibre directions. Furthermore, most research works based on thermography on composite material has shown that thermal analyses can indicate the damage location on the specimen surface and successfully detected the damage formation and propagation based on the temperature evolution under static loading conditions [13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies were also performed to investigate the evolution of composite damage under static tensile tests by using the thermography method with different fibre orientations of E-glass respective to the loading direction. These studies showed that the thermography method can locate the failure due to the rupture of fibre by detecting the hottest point of the specimen and it is very useful for early diagnostics of structures under real conditions [38,39]. Colombo et.al [40] in their study about mechanical characteristics of GFRP by thermography, categorised thermal behaviour of fibre composite into elastic behaviour, non-elastic behaviour and final breakage.…”
Section: Introductionmentioning
confidence: 99%
“…Such approach is common in the automotive industry. Other common applications of the active PVT scheme are in quantitative subsurface defect assessment (cracks, delaminations, impact damages, disbondings, moisture), thermophysical property evaluation; in all kind of industries (Myriounis et al, 2011;Lahiria et al, 2012;Naderi et al, 2012;Wu et al, 2011;Cheng and Tian, 2012;Kutin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%